Combined Acupuncture and Shirodhara a Complimentary Approach in the Management of Cerebral Venous Sinus Thrombosis (CVST): A Case Report - Satyal, Jaya; KC, Rachana; KC, Pradeep; Chandra, Avinash; Adhikari, Jhularam; Pant, Basant; Shrestha, Prajeet Kumar (Annapurna Journal of Health Sciences, 2025)
Cerebral Venous Sinus Thrombosis (CVST) is a rare and life-threatening neurological manifestation of anti-phospholipid syndrome that affects a small percentage of stroke cases, with headache being the main symptom. A 20-year-old male patient arrived at the emergency department with complaints of severe headache, photophobia, phonophobia, nausea, and vomiting lasting for the past 4 days. Conservative management was initially undertaken, but no significant therapeutic effect was observed. Therefore, an integrated approach combining Western medicine with acupuncture and Shirodhara was implemented for 14 days. The outcome measure for headache was assessed using the Visual Analog Scale (VAS) of pain. The initial VAS score was 10. On the last day of the intervention, the patient reported significant relief, with a VAS score of 1, and a notable improvement in vision. This case report highlights the effectiveness of acupuncture and Shirodhara in managing symptoms of cerebral venous sinus thrombosis.